Transparência ativa nas instituições da rede federal de educação, ciência e tecnologia da região norte brasileira - Costa, Fabrício Barbosa da (Universidade Federal do Tocantins, 2021)
The right to access information is an issue that has been increasingly debated over the years due to the search for transparency and democratic participation in society. The use of information technologies has facilitated social control and the requirement of rights by the population. Therefore, this research aimed to analyze the compliance with the legislation related to access to information, through the mechanism active transparency of the electronic portals of the Public Education Institutions belong Federal Network of Education, Science and Technology North Brazilian Region. This work is classified according to its objectives as descriptive and exploratory, with respect to nature is quantitative and qualitative, and as for the technical procedures, it consists of a documentary and bibliographic research. The data were collected using the systematic observation technique with the support of a guided navigation table, developed by the author based on the CGU's active transparency guide, which is mandatory use in public agencies of the Federal Executive Branch. The results show that, according to the average obtained by the group of institutions analyzed, the service occurs in only 51% of what was observed, in 33% the service is partially provided, and in 16% of the analyzed categories the entities do not comply with legislation.